The effects of a nonsteroidal anti-inflammatory drug on the degree of titanium implant osseointegration - Toy, Vesile Elif; Dundar, Serkan; Bozoglan, Alihan (Elsevier B.V., 2020)
Objective: The aim of this study was to histologically examine the effects of a nonsteroidal anti-inflammatory drug, namely diclofenac sodium (DCS), on the extent of the bone–implant contact (BIC) of titanium implants after four weeks of osseointegration period in a rodent model. Material & methods: Fourteen female Sprague-Dawley rats were divided into two groups: the control (n = 7) and experimental (DCS) groups. Fourteen machine-surfaced titanium implants were placed in the right tibial bones of the rats. The DCS (2 mg/kg) was administered by means of oral gavage to the experimental group for 14 days after four weeks of osseointegration. No medication was administered to the control group throughout the six-week study period. At the end of the study, the rodents were sacrificed and block sections were obtained for histologic evaluation. Results: The mean BIC ratios for the control and DCS groups were 64.15 ± 6.31% and 61.10 ± 6.08%, respectively. No statistically significant difference in terms of the BIC ratios was found between the two groups. Conclusion: The results of this study demonstrate that DCS did not impair the BIC of the implants after four weeks of osseointegration. © 2020 Craniofacial Research Foundation
Keywords: Bone implant connection; Diclofenac sodium; Nonsteroidal anti-inflammatory drug; Osseointegration